2013
DOI: 10.1111/cen.12302
|View full text |Cite
|
Sign up to set email alerts
|

Early morning salivary cortisol and cortisone, and adrenal responses to a simplified low‐dose short Synacthen test in children with asthma

Abstract: Our data illustrate that basal measures of cortisol are likely to be of value in screening populations for patients at greatest risk of adrenal crisis. EMSCn shows promise as a screening tool for the identification of patients with severe adrenal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 27 publications
1
37
1
Order By: Relevance
“…Cortisol concentrations in the early morning correlate strongly with peak cortisol concentrations in dynamic tests of adrenal function5 9 10 and have been reported to be helpful screening tests in children and young people. The sensitivity and specificity of a cortisol concentration <108 nmol/L at 9:00 for the diagnosis of adrenal insufficiency are reported to be 83% and 99%, respectively, while adrenal insufficiency is unlikely when 9:00 cortisol is >381 nmol/L 11…”
Section: Diagnostic Tests Of Adrenal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortisol concentrations in the early morning correlate strongly with peak cortisol concentrations in dynamic tests of adrenal function5 9 10 and have been reported to be helpful screening tests in children and young people. The sensitivity and specificity of a cortisol concentration <108 nmol/L at 9:00 for the diagnosis of adrenal insufficiency are reported to be 83% and 99%, respectively, while adrenal insufficiency is unlikely when 9:00 cortisol is >381 nmol/L 11…”
Section: Diagnostic Tests Of Adrenal Functionmentioning
confidence: 99%
“…The LDSST can be technically challenging; sampling at 5 min intervals is recommended for identification of cortisol peaks,25 although sampling at 10 min intervals may also be acceptable 5. The only available concentration of Synacthen is 250 µg/mL.…”
Section: Diagnostic Tests Of Adrenal Functionmentioning
confidence: 99%
“…Measurement of salivary cortisol is becoming routine in some clinics for the assessment of adrenal function. Late‐night salivary cortisol testing is now recommended as a first‐line diagnostic test in Cushing's syndrome, and there are reports of its use in the diagnosis of adrenal insufficiency . Advocates of salivary measurements favour its convenience and potential cost savings over serum sampling.…”
Section: Introductionmentioning
confidence: 99%
“…However, with increasing case reports of adrenal insufficiency with the use of ICS, the importance of understanding the risk factors associated with HPA suppression have become more obvious. In fact, some studies have shown that as many as 20-50% of children treated with ICS had biomedical abnormalities of the HPA axis (8). Fluticasone propionate is much more likely to cause clinically symptomatic adrenal suppression compared to other ICS like beclomethasone, triamcinolone and budesonide.…”
Section: Glucocorticoid and Childhood Asthmamentioning
confidence: 99%